Lexicography and Sign Language Engineering: The Zambian Experience - Chanda, Vincent M. (Lexikos, 1997)
Sign language as used by deaf communities, is a real and fully-fledged human language, not based on any spoken language, and not universal in the sense of there being only one sign language worldwide. A deaf community is a linguistic minority, but a linguistic minority with special linguistic needs because of the very nature of sign language. In Zambia, like in the vast majority of other Third World countries, the linguistic needs of deaf and hard-of-hearing people have been ignored. This article examines the genesis and implementation of a dictionary project for sign language, the Zambian Sign Language Dictionary Project, regarded as a first step towards the development of a Zambian National Sign Language. The article highlights the specificity of sign language lexicography.